Occupational Safety and Health Management System in Procurement of Goods and Warship Repair Services - Subakti, I Made (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Warship repair is a work that contains quite high risks, especially when carrying out work in a narrow workspace, resulting in difficulties in placing lifting equipment, minimal use of body harnesses, and the large number of closed spaces that allow the accumulation of CO2 gas. To overcome existing risks, this study was conducted to determine the influence, the supporting and inhibiting factors, and the ideal system for occupational safety and health management as well as the goods and services procurement for warship repairs. The approach used in this study is a mixed method by conducting a purposive sampling questionnaire on stakeholder respondents involved in warship repairs. Processing the data from the questionnaire using the SEM method with Amos software. This study shows that the occupational safety and health management system has a significant influence on the implementation of the procurement of goods and services as well as the readiness of warships but procurement of goods and services does not have a significant effect on warship readiness. The supporting factors for optimizing the implementation model for procurement of goods and services with an occupational safety and health management system in warship repairs include workforce skills, adequate work equipment, warship repair work methods, understanding of material properties, effectiveness, competition, and procurement accountability for goods and services. Meanwhile, the inhibiting factors are the unavailability of appropriate lifting equipment, the condition of warship infrastructure, efficiency, transparency, and openness. The occupational safety and health management system model and implementation of procurement of goods and services that can optimize warship repairs are achieved by displaying variables that are supporting factors and providing additional clauses in procurement documents.